Exploring the Influencing Factors of Digital Transformation Effectiveness of Specialized and Sophisticated SMEs - Chen, Xinhui; Shi, Yuting; Feng, Zixun (Journal of Global Economy, Business and Finance, 2024)
Digital transformation is a significant strategy for enterprises to implement long-term business growth and high-quality development. This paper identifies the factors affecting the effectiveness of digital transformation of specialized and sophisticated SMEs; explores the configuration path of the six antecedent factors that jointly drive the enterprise to achieve high-effective digital transformation by using fuzzy-set qualitative comparative analysis. The findings illustrate no single factor can be a necessary and sufficient condition for the formation of the outcome variable; There are three main configuration paths that lead to a high-impact corporate digital transformation, which can be categorized as total factor driven, organization-environment oriented, and organization-environment dominated. As the most energetic and high-quality group of SMEs, Specialized and sophisticated SMEs plays an exemplary leading role in the direction of digital transformation. Therefore, the research sample in this paper is representative and provides some reference indicators for the government to formulate support policies, and also enlighten the thinking of other small and medium-sized enterprises on digital transformation. In addition, this paper explore concludes the key factors and configuration paths that influence the transformation effectiveness of Specialized and Sophisticated SMEs, which could provide practical guidance for managers to formulate digital transformation strategies and paths.